Developing ambidexterity and resilience: The predictive role of high-performance work systems - Charles Hanu; Njabulo Khumalo (SA Journal of Human Resource Management, 2023)
Orientation: Organisations and employees face crises at a point in time that may disrupt their normal work activities. High-performance work systems (HPWSs) help develop and enhance individuals’ and firms’ ability to respond to crises effectively.